E.M. Forster and the Writing of Empire: Aestheticentrism, Humanism, and Liberal Guilt - Mokrani Barkaoui, Selma (Journal of Human Sciences, 2010)
This study suggests a different mode of viewing the contradictions inherent in E.M. Forster’s standing with regard to the British Empire. It contests the view that Forster is an anti-imperialist by making use of a wider range of his non-fictional writings. It also makes use of biographical proof to demonstrate that Forster was personally involved in the project of the British Empire, and therefore, complicit in the imperial venture. Forster’s attitude towards his country’s imperial dash is gauged within the context of his intellectual and literary relations with the Bloomsbury group.               The mercurial quality of his discourse about the imperial circumstances is analysed in order to highlight the perfunctory, self-reflexive nature of his compassion with the “natives.”